Patient Perspectives on Quality of Health Services in Mulyorejo Public Health Centre - Ramadansa Berlian, Eranio; Sri Redjeki, Endang; Mawarni, Dian (KnE Life Sciences, 2021)
The quality of service of a healthcare facility has a direct impact on the community’s perception of it, which can be seen from the level of patient visits. Mulyorejo is one of the 15 public health centres in Malang city with one type of service facility – the general clinic. According to the health profile data of Malang city, in 2017, the number of outpatient visits at Mulyorejo Public Health Centre was 28,462, which increased to 43,101 in 2018. However, based on secondary data that has been obtained, from January to September 2019, the number of patients visiting the Mulyorejo Public Health Centre decreased. This research is a descriptive study with a quantitative approach and a sample size of 70 people, selected through the incidental sampling technique. The data source used is the primary data obtained directly from the distribution of the modified HCAHPS (hospital consumers assessment of healthcare providers and systems) questionnaire to respondents. Based on the final results, the average score on the quality of health services at the Mulyorejo Public Health Centre based on the perceptions of the general poly-patients at the Mulyorejo Public Health Centre was rated “b,” which means that the quality of health services at the Mulyorejo Public Health Centre is good. Keywords: quality of health services, patient perspectives, public health centre